1993
DOI: 10.1111/j.1365-3032.1993.tb00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Source of an egg kairomone for Trissolcus basalis, a parasitoid of Nezara viridula

Abstract: The eggs of the southern green stink bug, Nezara viridula (L.) (Hemiptera: Pentatomidae), are successfully attacked by Trissolcus basalis (Woll.) (Hymenoptera: Scelionidae) and are recognized as hosts by a secretion applied to the egg chorion. This secretion is produced by the follicular cells in the proximal region of the ovanole of the female pentatomid and functions as an adhesive for attaching the eggs to the oviposition substrate. The adhesive and kairomone activity could be partially removed with water. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 13 publications
3
89
0
4
Order By: Relevance
“…The selective response toward a specific host (E. heros) for three of the five species evaluated could suggest that these parasitoids use cues from host egg masses to identify those that would maximize their reproductive success. These cues could be related to physical (color, size, number and disposition of eggs, chorion thickness, corion ornamentation) and chemical (semiochemical) characteristics of the egg masses (Bin et al, 1993;Borges et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The selective response toward a specific host (E. heros) for three of the five species evaluated could suggest that these parasitoids use cues from host egg masses to identify those that would maximize their reproductive success. These cues could be related to physical (color, size, number and disposition of eggs, chorion thickness, corion ornamentation) and chemical (semiochemical) characteristics of the egg masses (Bin et al, 1993;Borges et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…These tests were run using two combinations: (1) oviposition on female traces and tested on female traces (female_kairomone_female, f_ko_f, N=34) or (2) oviposition on male traces and tested on male traces (male_kairomone_male, m_ko_m, N=30). For T. basalis females, successful oviposition is known to increase klinokinesis and decrease orthokinesis in a manner analogous to contact with host chemical residues (Bin et al, 1993). Thus, to separate the effect of oviposition experience and host chemical residues, experienced female wasps tested on uncontaminated areas were used as controls, leading to two additional treatments: (3) oviposition on female residues and tested on uncontaminated arena (female_kairomone_blank, f_ko_b, N=15), or (4) oviposition on male residues and tested on uncontaminated arena (male_kairomone_blank, m_ko_b, N=15).…”
Section: Oviposition Experiencementioning
confidence: 99%
“…According to VINSON (1998), changes in behaviour related to host age can be due to alterations in the chemical stimuli, the physical stimuli (shape, colour, size, resonance, among others) or physical conditions (membranous barriers) assessed by the wasps when recognizing and accepting hosts. In the Scelionidae, various sources demonstrate host acceptance to occur only given appropriate chemical stimuli (STRAND & VINSON, 1983;BIN et al, 1993), and many of these stimuli can become less evident with host age, implying in increased difficulty for host recognition (VINSON, 1998). Studies done by STRAND & VINSON (1983) showed that Telenomus heliothidis (Ashmead, 1853) (Hymenoptera, Scelionidae) detects host age through antennal drumming, using host egg format of Heliothis virecesns (Fabricius, 1777) (Lepidoptera, Noctuidae), which becomes less spherical and more conical with increases in age.…”
Section: Resultsmentioning
confidence: 99%